Study on the transient expression of infectious bronchitis virus spike protein in Nicotiana benthamiana leaves - Tra, Nguyen Thi; Hong Duong, Ngo; Thai Vy, Trinh; Tra My, Le Thi; Thu Hien, Nguyen Thi; Van, Pham Thi; Thanh Huong, Doan Thi; Bich Ngoc, Pham; Hoang Ha, Chu; Thu Hang, Hoang Thi (Vietnam Journal of Biotechnology, 2023)
Infectious bronchitis virus (IBV) is considered as one of the main causes of economic loss in chicken farms worldwide, especially in poultry producing nations. This virus, a member of the Coronaviridae family, is classified into different genotypes based on its surface spike glycoproteins which also play important roles in cell attachment and immune response. Due to continual genetic mutation of IBV, attenuated and inactivated vaccines show decreased effectiveness or lack of cross – protection; thus ongoing studies focus on the development of new generation vaccines to prevent new IBV outbreaks. This paper describes our study on expression of the antigenic region in S1 subunit of the spike in Nicotiana benthamiana. Two expression vectors carrying either S1 or receptor binding domain (RBD) coding gene (pCB301-S1 and pCB301-RBD) were constructed and transformed into tobacco leaves by agroinfiltration method. The RBD showed a clearly higher level of expression compared to the whole S1. Purification of RBD by immobilized metal ion chromatography and size exclusion chromatography represented a mixture of monomer, dimer and trimer glycoprotein with expected sizes in Western blot. In summary, this study demonstrated our primary success in establishing an expression model that could be used to investigate plant-based IBV recombinant vaccine.